EFEK PEMBERIAN EKSTRAK ETANOL RIMPANG JERINGAU TERHADAP GAMBARAN MORFOHISTOLOGI GINJAL TIKUS PASCA INDUKSI NATRIUM NITRIT - Muhammad zaharul ichsan (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
Long-term use of NaNO2 in food preservatives causes a variety of health problems, particularly for kidney function. Natural antioxidants that can reduce the effects of free radicals are required to prevent these effects. The sweet flag plant is a medicinal plant with high antioxidant potential. This study aims to determine the effect of sweet flag rhizome extract (SFRE) on the morphology and histology of the kidneys of white rats induced by NaNO2. This study used 25rats with 5 groups. Negative control was given CMC0,5% for 40 days, positive control was given NaNO2. dose of 50 mg/kgBW on days 1-30 and CMC0.5% on days 16-40, treatment groups 1, 2 and 3 were given NaNO2 Dosage of 50 mg/kgBW on days 1-15, on days 16-30 was given NaNO2 Dosage of 50 mg/kg BW+SFRE, on days 31-40 only given SFRE in graded doses (T1=250,T2=500, and T3=750 mg/kgBW). The results obtained include SFRE has no effect on kidney morphology. However, SFRE affects the diameter of the distal and proximal tubules with both tubules getting Pvalue=0.000. SFRE had an effect on the score of histological damage with Pvalue=0.017. The safe and optimal dose of SFRE to improve renal histology is a dose of 250 mg/kg BW.